Fertilizer industry uses Global Yield Gap Atlas (GYGA) for long term minimum nutrient requirements estimates targeting enhanced productivity and minimum GHG emissions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Establishing minimum long term N input requirements for defined target yields is an essential part of any sustainable soil management strategy and low-emission development. We developed such benchmark data, which are currently taken up by the fertilizer industry to transition to long term sustainable crop nutrient management, which ensures soil fertility maintenance and high productivity while reducing GHG emissions.